Total polyphenol content and antioxidant activity of commercial Noni (Morinda citrifolia L.) juice and its components - Adriana Bramorski; Adriana da Rosa Cherem; Chaiana Paula Marmentini; Joseane Torresani; Tatiana Mezadri; Andréa de Almeida Silva Costa (Universidade de São Paulo, 2010)
The plant Morinda citrifolia L. (noni) has been the focus of many recent studies due to its potential effects on treatment and prevention of several diseases. However, there are few in vivo and in vitro studies concerning its composition and antioxidant capacity. The aim of the present study was to determine the total polyphenol content (TPC) and antioxidant capacity of a juice commercialized as noni juice, but containing grape, blueberry and noni fruits. Commercial noni juice was compared against its separate constituents of blueberry and grape juice. Folin-Ciocalteu and DPPH• methods were used to determine the concentration of total polyphenol content and antioxidant activity, respectively. Commercial noni juice presented higher values of TPC (91.90 mg of gallic acid/100 mL juice) and antioxidant activity (5.85 mmol/L) compared to its 5% diluted constituents. Concentrated blueberry juice presented higher TPC and antioxidant activity than the other juices analyzed. Considering that the blueberry and grape juices account for only 10% in the composition of commercial noni juice, it can be inferred that these two components contribute significantly to the antioxidant activity. Therefore, additional studies are necessary in order to elucidate the contribution of the noni juice as an antioxidant. A planta Morinda citrifolia L. tem sido objeto de muitas pesquisas decorrente de seus efeitos benéficos no tratamento e prevenção de muitas doenças. No entanto, são escassos os estudos in vivo e in vitro sobre os compostos presentes e sua capacidade de atuar como antioxidante. Objetivou-se com este trabalho determinar o índice de polifenóis totais (IPT) e a capacidade antioxidante do suco de noni comercial, constituído de uva, mirtilo e a fruta do noni. O suco de noni comercial foi comparado com seus constituintes (mirtilo e suco de uva) separadamente. Os métodos Folin-Ciocalteu e DPPH• foram utilizados para determinar a concentração de polifenóis totais e capacidade antioxidante, respectivamente. O suco de noni apresentou valores superiores de IPT (91,90 mg ácido gálico/100 mL de suco) e atividade antioxidante (5,85 mmol/L) quando comparado aos seus constituintes diluídos a 5%. O suco de mirtilo, na sua forma concentrada, apresentou IPT e atividade antioxidante superior aos demais sucos. Considerando que os sucos de mirtilo e de uva representam apenas 10% na composição do suco de noni, pode-se inferir que estes dois constituintes contribuem de forma significativa para a atividade antioxidante. Assim, estudos adicionais são necessários para elucidar a contribuição do suco de noni como sequestrador de radicais livres.